Monitoring Corporate Compliance through Cooperative Federalism: Trends in Multistate Settlements by State Attorneys General. Issue 3 (4th June 2022) - Provost, Colin; Dishman, Elysa; Nolette, Paul
Abstract: Recent scholarship on U.S. regulatory federalism has tended to focus on conflict between the states and state resistance to federal initiatives. Less attention has been given to federal–state cooperation and how it affects regulatory enforcement. In this article, we examine intergovernmental cooperation in multistate lawsuits filed by state attorneys general to ascertain trends in multistate regulatory enforcement through litigation over time. We pay particular attention to the increasing use of compliance monitoring by both state and federal regulators, including through monitors independent of the regulated industries. Relying upon a dataset of legal settlements, scoping interviews, and two case studies of recent multistate litigation, we find that federal–state cooperation in multistate lawsuits has become more institutionalized over time. This increased cooperation has created a two-way street in which state and federal regulators often combine resources and learn from each other through the process of compliance monitoring.